Faktor Penyebab dan Strategi Mengatasi Kecemasan Matematika dalam Pembelajaran: Systematic Literature Review - Nasywa Alya Syafitri; Anggun Badu Kusuma (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Mathematics anxiety is an uncomfortable feeling such as worry, fear, and tension when students face a mathematics test. This study aims to identify the factors that cause mathematics anxiety and effective strategies to overcome it in mathematics learning. The method used is a Systematic Literature Review (SLR) with the PRISMA approach, which includes the stages of identification, screening, eligibility, and inclusion. Data were obtained from 75 articles sourced from Google Scholar, then selected based on inclusion and exclusion criteria until 40 suitable articles were obtained. Data analysis was carried out qualitatively through content analysis techniques by grouping the findings into categories of causal factors and strategies for overcoming mathematics anxiety. The results of the study indicate that mathematics anxiety is influenced by internal factors, such as self-confidence, cognitive abilities, and emotional conditions, as well as external factors, such as teaching methods, the learning environment, and learning pressure. Mathematics anxiety has been shown to negatively impact the process and outcomes of student learning. Therefore, appropriate strategies are needed to overcome it, including through the implementation of varied and enjoyable learning, the use of visual thinking strategies, student-centered learning, the implementation of active learning in the classroom, the creation of a comfortable learning atmosphere, and support through training programs and parental guidance. However, this research was based solely on a literature review without involving direct field data. Therefore, it is recommended that further research be conducted directly in the field to obtain more accurate results on students' math anxiety